Optimizing Corporate Social Responsibility in the Plantation Sector: A Legal and Socio-Empirical Approach - Sari, Rayon; Sudirman, Lu; Nurlaily, Nurlaily (Universitas Internasional Batam, 2025)
Corporate Social Responsibility (CSR) is a vital component of modern corporate governance, particularly in environmentally and socially sensitive sectors such as plantations. In Indonesia, although the legal framework for CSR is established through Company Law and sectoral regulations, its implementation often lacks strategic depth and sustainability. This study investigates the legal and empirical challenges of CSR practices within the non-palm plantation sector, focusing on how companies translate normative CSR obligations into effective, community-centered programs. The research aims to evaluate the effectiveness of CSR as a tool for sustainable development, identify gaps between regulatory expectations and field practices, and propose recommendations for optimization. Using an empirical juridical method, this study combines qualitative interviews with legal analysis of CSR frameworks to assess social and environmental outcomes of CSR programs. Findings reveal that CSR is frequently treated as a compliance obligation, with many initiatives lacking integration into long-term business strategy. Programs are often symbolic, with limited tangible benefits for local communities due to weak regulatory coordination, inadequate stakeholder engagement, and ineffective monitoring. The study concludes that CSR in the plantation sector requires a transformative shift—from superficial compliance to strategic sustainability. Integrating CSR into business core values, supported by clear legal standards, inclusive stakeholder collaboration, and transparent reporting, is essential to enhance its real-world impact. This research offers a model for evaluating CSR effectiveness and contributes to the broader discourse on legal reform and sustainable corporate governance in Indonesia’s agribusiness sector.